Transmission of an Epstein−Barr strain common in south-east China to a western individual - Poirey, Rémy; Delecluse, Henri-Jacques; Delecluse, Susanne (Journal of medical virology, 2024)
Epstein−Barr virus strains present in South-East Asia are tightly associated with nasopharyngeal carcinomas. We report the case of a Caucasian female who presented with an infectious mononucleosis syndrome. Sequencing demonstrated that she had been infected with a virus of Chinese origin that is thus spreading into European countries.
Zuerst veröffentlicht: 09. Dezember 2024
Gesehen am 14.03.2025